Near-infrared fluorophores methylene blue for targeted imaging of the stomach in intraoperative navigation - Wang, Zhidong; Mei, Lin; Yang, Xiao; Jiang, Tiantian; Sun, Tingkai; Su, Yuanhao; Wu, Youshen; Ji, Yuanyuan (Frontiers in Bioengineering and Biotechnology, 2023)
Near-infrared (NIR) fluorescence imaging-guided surgery is increasingly concerned in gastrointestinal surgery because it can potentially improve clinical outcomes. This new technique can provide intraoperative image guidance for surgical margin evaluation and help surgeons examine residual lesions and small tumors during surgery. NIR fluorophores methylene blue (MB) is a promising fluorescent probe because of its safety and intraoperative imaging in the clinic. However, whether MB possesses the potential to perform intraoperative navigation of the stomach and gastric tumors needs to be further explored. Therefore, the current study mainly validated MB's usefulness in animal models' intraoperative imaging of stomach and gastric tumors. NIR fluorophores MB can exhibit specific uptake by the gastric epithelial cells and cancer cells. It is primarily found that MB can directly target the stomach in mice. Interestingly, MB was applied for the NIR imaging of gastric cancer cell xenografts, suggesting that MB cannot specifically target subcutaneous and orthotopic gastric tumors in xenograft models. Thus, it can be concluded that MB has no inherent specificity for gastric tumors but specificity for gastric tissues. Apparently, MB-positive and negative NIR imaging are meaningful in targeting gastric tissues and tumors. MB is expected to represent a helpful NIR agent to secure precise resection margins during the gastrectomy and resection of gastric tumors.